2015
DOI: 10.1016/j.juro.2015.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Target Inhibition of IL-1 Receptor Prevents Ifosfamide Induced Hemorrhagic Cystitis in Mice

Abstract: Anakinra is effective for preventing experimentally ifosfamide induced hemorrhagic cystitis. It seems that neutrophil and macrophage infiltration in this circumstance depends on IL-1 signaling through IL1R. Possibly TNFR2 has a protective role in hemorrhagic cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Besides verifying that IPSE indeed could dampen ifosfamide-triggered hemorrhagic cystitis in an IL-4-dependent manner, we also found that many of IPSE's effects in this model relied upon an intact nuclear localization sequence [7,23]. In a subsequent RNA-Seq-based analysis, we confirmed that gene transcription related to TNF signaling is upregulated in ifosfamide-induced hemorrhagic cystitis [24], as reported by others using alternative experimental approaches [25,26]. Moreover, through this analysis we discovered that IPSE reduces expression of ifosfamide-induced genes related to the TNF pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Besides verifying that IPSE indeed could dampen ifosfamide-triggered hemorrhagic cystitis in an IL-4-dependent manner, we also found that many of IPSE's effects in this model relied upon an intact nuclear localization sequence [7,23]. In a subsequent RNA-Seq-based analysis, we confirmed that gene transcription related to TNF signaling is upregulated in ifosfamide-induced hemorrhagic cystitis [24], as reported by others using alternative experimental approaches [25,26]. Moreover, through this analysis we discovered that IPSE reduces expression of ifosfamide-induced genes related to the TNF pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Most probably, IL‐1β and IL‐6 are particularly involved in the toxic effects reported after CYP administration. It was shown that an IL‐1 receptor blocker (ie, anakinra) reduced hemorrhage and inflammatory response after CYP‐treatment in rodents as well as improved the functional bladder parameters . Moreover, via induction if the inducible iNOS, IL‐1β (and TNF‐α) mediates generation of NO .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that an IL-1 receptor blocker (ie, anakinra) reduced hemorrhage and inflammatory response after CYP-treatment in rodents as well as improved the functional bladder parameters. 22 Moreover, via induction if the inducible iNOS, IL-1β (and TNF-α) mediates generation of NO. 2 It was shown that inhibition of TNF-α and IL-1β diminished the urothelial erosion, hemorrhage, edema, and leukocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…The transition of the bladder mucosa from a homeostatic innate immune response to acute disease reflects the molecular control of IL-1β processing, through inflammasome-dependent or non-canonical mechanisms ( Fig 8 ), [ 44 46 ]. The findings suggest that acute cystitis might resemble hyper-inflammatory disorders [ 28 , 47 , 48 ], where therapeutic efficacy of IL-1β inhibitors has been documented [ 49 , 50 ]. The results provide a molecular context for acute cystitis and for the susceptibility to acute cystitis in patients with severe and chronic disease.…”
Section: Discussionmentioning
confidence: 99%